Hydrogel with good biological adhesion as well as preparation method and application thereof
By preparing loose porous hydrogels with oxidized dextran and adipic acid dihydrazide modified hyaluronic acid as matrix, loading TAX@ZIF-8@PDA, the problem of poor adhesion of hydrogel is solved, and the precise release of drugs and the improvement of bone repair effect is achieved, and good biocompatibility and antibacterial properties are also provided.
Patent Information
- Application Number
- CN202510062459.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Existing hydrogels have poor adhesion in bone defect areas and are difficult to adhere firmly, resulting in inaccurate drug release, reducing bone repair effect, and increasing medical costs.
Loose porous hydrogels with oxidized dextran and adipic acid dihydrazide modified hyaluronic acid as matrix were prepared by Schiff base reaction. They were loaded with TAX@ZIF-8@PDA, and the adhesion was significantly improved by synergistic action between PDA and hydrogel, and showed good biostability and antibacterial properties under near-infrared irradiation.
It significantly improves the adhesion and biocompatibility of the hydrogel, ensures the precision and continuous effect of the drug on bone defects, improves bone repair effect, reduces medical costs, and has excellent antibacterial and antioxidant properties.
Smart Images

Figure BDA0005243295370000061 
Figure BDA0005243295370000081 
Figure HDA0005243295380000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medicine and relates to wound dressings, and in particular to a hydrogel with good bioadhesion and a preparation method and application thereof. Background Art
[0002] In recent years, the incidence of fractures and large-area bone defects has shown an increasing trend year by year, which has brought a huge burden to medical care and the economy, and has also seriously affected people's quality of life. In clinical treatment, autologous bone transplantation and allogeneic bone transplantation are regarded as the two core solutions to the problem of large-area bone defects. In order to solve the limitations of bone in the donor site (limited bone source and size), bone tissue engineering (BTE) has been developed to repair bone defects, aiming to replace traditional transplantation methods with this technology for efficient repair of bone defects. As an ideal BTE scaffold candidate, hydrogel has a porous structure similar to the extracellular matrix (ECM) and has good biocompatibility.
[0003] The applicant previously designed an injectable intelligent controlled-release hydrogel and its application in the treatment of bone injuries (application number: 2024103570481). The hydrogel uses Pht as the active ingredient, uses ZIF-8 nanoparticles as a carrier, and PDA as a nanoparticle coating. After irradiation with near-infrared light, Pht and Zn 2+ Intelligent on-demand release and efficient transportation can not only make drugs more effectively penetrate into bone tissue and deliver drugs more accurately, but also further improve bone repair effects and achieve repair of critical-sized bone defects. However, the hydrogel has poor adhesion and is difficult to adhere firmly to the bone defect site. It is easy to shift and fall off, which is not conducive to providing a stable support environment for bone defect repair. In addition, due to poor adhesion, the drug cannot act accurately and continuously on the defect site, reducing the effect of drug treatment. At the same time, frequent replacement of hydrogel materials also increases medical costs. Summary of the invention
[0004] In view of the above technical problems and defects, the object of the present invention is to provide a hydrogel with good bioadhesion. The hydrogel is prepared into a loose porous hydrogel by Schiff base reaction of oxidized dextran (ODEX) and HA (HD) modified by adipic acid dihydrazide (ADH). TAX@ZIF-8@PDA is loaded in the hydrogel. The synergistic effect of TAX@ZIF-8@PDA and ODEX-HD significantly improves the adhesion of the hydrogel. It exhibits good biostability and biocompatibility under near-infrared irradiation, and has excellent antibacterial and antioxidant properties. During the bone tissue generation process, it can enhance the osteogenesis ability and promote the repair of critical bone defect sites.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A hydrogel with good bioadhesion is prepared into a loose and porous hydrogel by reacting oxidized dextran with hyaluronic acid modified with adipic acid dihydrazide through a Schiff base reaction, and TAX@ZIF-8@PDA is loaded in the hydrogel. The preparation method of the TAX@ZIF-8@PDA is as follows: firstly encapsulating TAX in ZIF-8 nanoparticles to obtain TAX@ZIF-8 nanoparticles; then wrapping PDA on the surface of the TAX@ZIF-8 nanoparticles; wherein TAX is dihydroquercetin, ZIF-8 is a zinc-based zeolite imidazole skeleton, and PDA is polydopamine.
[0007] The present invention also provides a method for preparing a hydrogel with good bioadhesion, the method comprising the following steps:
[0008] Step 1. First, TAX is encapsulated in ZIF-8 nanoparticles to obtain TAX@ZIF-8 nanoparticles; then, PDA is coated on the surface of TAX@ZIF-8 nanoparticles to obtain TAX@ZIF-8@PDA;
[0009] Step 2. Using oxidized dextran aqueous solution and adipic acid dihydrazide-modified hyaluronic acid aqueous solution as the matrix, TAX@ZIF-8@PDA was added to 10% oxidized dextran aqueous solution, followed by adding 3 times the amount of 5% adipic acid dihydrazide-modified hyaluronic acid aqueous solution to prepare a hydrogel with good bioadhesion.
[0010] As a preferred embodiment of the present invention, in step 1, the preparation method of TAX@ZIF-8 nanoparticles is: dissolving 0.36g TAX and 0.5g 2-methylimidazole in 5mL methanol solution; then dissolving 0.1g zinc nitrate hexahydrate in 5mL methanol, mixing the two and stirring for 30min, then centrifuging, drying and precipitating, and obtaining TAX@ZIF-8NPs;
[0011] The preparation method of TAX@ZIF-8@PDA is as follows: 8 mg of TAX@ZIF-8NPs are dispersed in a Tris-HCl solution, 2 mg of dopamine hydrochloride is added, stirred for 2 h, centrifuged, and the precipitate is dried to obtain TAX@ZIF-8@PDA NPs.
[0012] As a preferred embodiment of the present invention, in step 2, the preparation method of hyaluronic acid modified with adipic acid dihydrazide is as follows: 1 g HA is dissolved in 500 mL MES buffer, and then EDC and NHS are added to activate the carboxyl groups in HA for 4 hours; then, 1 g adipic acid dihydrazide is added to the reaction mixture and stirred at room temperature for another 24 hours; the crude product is subjected to enhanced dialysis under 0.1 M NaCl and deionized water conditions, and freeze-dried to obtain HD, i.e., adipic acid dihydrazide-modified HA.
[0013] As a preferred embodiment of the present invention, the TAX concentration in the hydrogel with good bioadhesion is 250 μg / mL.
[0014] The hydrogel with good bioadhesion provided by the present invention is beneficial to the proliferation of osteoblasts, can enhance the osteogenic differentiation and calcium deposition ability of osteoblasts, upregulate osteogenic markers such as osteogenic genes alkaline phosphatase (ALP) and Osterix (OSX), and has a positive effect on the repair of bone defects and new bone formation; and in vivo bone reconstruction experiments show that rats irradiated with TZTG+NIR show excellent therapeutic effects in accelerating in vivo osteogenesis and repair, and the critical bone defects are basically healed after 8 weeks of treatment. Therefore, it can be used in the preparation of biological scaffolds that promote bone repair.
[0015] After being irradiated with near-infrared light (NIR), the hydrogel of the present invention can be locally heated to a suitable temperature without damaging surrounding healthy cells. It has excellent photothermal conversion efficiency and good photothermal stability, so it can be used in the preparation of photothermal conversion materials.
[0016] Advantages and beneficial effects of the present invention:
[0017] (1) The hydrogel provided by the present invention loads PDA on the surface of TAX@ZIF-8 (TZ particles) nanoparticles to form a coating. After the TZ particles are coated with PDA, the positive charge is converted to negative charge, and the synthesized TAX@ZIF-8@PDA nanoparticles have a relatively large negative ζ value, which not only improves the dispersibility of the TZ particles and realizes the surface functionalization of the TZ particles, but also controls the slow release of the loaded drug (TAX) (which can be released for up to 30 days), ensuring that TAX is released at an appropriate speed and concentration during the entire bone reconstruction process, so that the active ingredients can play a long-term and continuous role, thereby accelerating bone defect repair; in addition, the synergistic effect of PDA and the hydrogel substrate can also significantly enhance the adhesion performance of the hydrogel, so that the hydrogel can firmly adhere to the bone defect site, accurately and continuously act on the defect, provide a stable support environment for bone defect repair, and accelerate the osteogenesis process.
[0018] (2) The hydrogel provided by the present invention has a loose porous structure. Such a loose porous internal morphology is conducive to the transport of the drug molecules (TAX) loaded inside, and is also conducive to the entry of oxygen and nutrients and the discharge of metabolites, thereby effectively promoting bone repair.
[0019] (3) The PDA in the hydrogel provided by the present invention can effectively absorb near-infrared light to achieve photothermal conversion, and it has a long-term photothermal conversion function. The photothermal conversion efficiency (η) of TZPG is 51.79%. TZPG with high photothermal conversion efficiency converts light energy into thermal energy and transfers the effectively generated heat to different positions of the bone defect, accelerating the stimulation of bone mesenchymal stem cells (BMSCs) towards osteogenic differentiation, promoting the repair and regeneration of bone tissue at low power, and improving the bone repair efficacy.
[0020] (4) The synergistic effect of ZIF-8, TAX and NIR-induced photothermal radiation in the hydrogel provided by the present invention is antibacterial, with an inhibition rate of up to 99.63±0.13% against Staphylococcus aureus and 96.93±0.36% against Escherichia coli. It has excellent antibacterial properties and can effectively prevent infection during bone defect repair.
[0021] (5) The hydrogel provided by the present invention has good swelling properties and can absorb tissue exudates. It also has excellent antioxidant activity and can remove ROS generated at the bone defect site, which is beneficial to improving the ability of oxidative stress to occur during bone regeneration and promoting bone healing.
[0022] (6) The hydrogel provided by the present invention has good biocompatibility, biodegradability and bioadhesion, which can ensure safety and non-toxicity during use; and it can promote the proliferation and growth of MC3T3-E1 cells, thereby promoting bone tissue formation.
[0023] (7) The hydrogel provided by the present invention can significantly promote the proliferation and osteogenic differentiation of MC3T3-E1 cells, improve osteogenic activity, and accelerate wound healing and bone tissue regeneration under 808 nm laser irradiation and synergistic treatment with near-infrared light.
[0024] (8) The hydrogel provided by the present invention can promote the inward growth of bone tissue in three-dimensional space. During the bone regeneration process, it can not only continuously release TAX to accelerate the formation of new bone, but also play the role of phased photothermal antibacterial and biomineralization to promote bone healing, promote bone regeneration in the rat bone defect model, and minimize the damage to healthy tissue caused by excessive heat production (the temperature of the TZPG group can rise to 45.1°C under near-infrared irradiation power). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1Characterization of ZIF-8, TAX@ZIF-8, and TAX@ZIF-8@PDANPs. A. TEM images of ZIF-8, TZ, and TZP (scale bar = 100 nm, 100 nm, and 50 nm); B. XRD spectra of TAX, ZIF-8, TZ, and TZP samples; C. Zeta potential of ZIF-8, TZ, and TZP. The bar graphs represent the mean ± SD.
[0026] Figure 2 Preparation and characterization of nanocomposite hydrogels. A. IR spectra of TAX, ZIF-8, TZ, and TZP; BE. IR spectra and 1HNMR spectra of DEX, ODEX, HA, and HA-ADH; F. SEM images of nanocomposite hydrogels (scale bars = 50 μm, 20 μm, and 10 μm).
[0027] Figure 3 The physicochemical characteristics and mechanical properties of nanocomposite hydrogels. A. Cumulative drug release of TG, TZG, and TZPG+NIR; B. Degradation rate of hydrogel; C. Swelling rate of hydrogel; D. Adhesion fracture force; E, F. Rheological analysis of hydrogel. The bar graphs represent the mean ± SD.
[0028] Figure 4 The mild photothermal effect of TZPG further stimulated bone formation. A. In vitro infrared thermogram. B. Photothermal temperature rise curves of TZP particle hydrogels with different concentrations. C. Heating and cooling curves of TZPG. D. Linear time data (lnθ) obtained from the cooling cycle of panel B. E. Photothermal stability curve of TZPG.
[0029] Figure 5 In vitro activity study. A. Inhibition images of E. coli and Staphylococcus aureus. B. Inhibition rates of E. coli and Staphylococcus aureus. C, D. Antioxidant activity (C. ABTS; D. DPPH). Bar graphs represent mean ± SD.
[0030] Figure 6 In vitro biocompatibility activity and osteogenic properties study. A. Hemolysis test B. Cell viability C. ARS image. The bar graph represents the mean ± SD.
[0031] Figure 7In vivo surgery and Micro-CT analysis. A. Schematic diagram of the surgery of the skull defect model. B. TZPG near-infrared thermal imaging of the defect site. C. Three-dimensional reconstruction of the skull. D. Trabecular separation (Tb.Sp). E. Trabecular thickness (Tb.Th). F. Number of trabeculae (Tb.N). G. Bone tissue volume / total tissue volume (BV / TV). The bar graph represents the mean ± SD. (*p<0.05, **p<0.01, ***p<0.001 represent comparisons with the control group).
[0032] Figure 8 A. Histopathology and immunohistochemical staining. AH&E and Masson staining images: newly formed bone (NB) and fibrous tissue (FT). B. Immunohistochemical staining of ALP, RUNX2, OPN, and COL-I. C. Quantitative analysis of OPN expression. D. Quantitative analysis of OCN expression. E. Quantitative analysis of ALP expression. F. Quantitative analysis of BMP2 expression. The bar graphs represent mean ± SD. (*p<0.05, **p<0.01, ***p<0.001 compared with the control group)
[0033] Fig. 9 Western blot analysis. A, BG analysis of ALP, RUNX2, OSX, OCN, COL-I and PDGFA protein expression levels; bar graphs represent mean ± SD. (*p < 0.05, **p < 0.01, ***p < 0.001 compared with the control group). DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific examples, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0035] 1.1 Materials
[0036] Taxifolin (TAX, purity ≥ 98.0%), sodium periodate (NaIO4, purity ≥ 99.5%), adipic acid dihydrazide (ADH, purity ≥ 98%), N-hydroxysuccinimide (NHS, purity ≥ 99.0%), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC, purity ≥ 99.0%), 2-methylimidazole (2-MeIm, purity ≥ 98.0%), dopamine hydrochloride (DA, purity ≥ 98.0%), methanol (MeOH, purity ≥ 99.5%), and TritonX-100 were provided by McCollum Biochemical Co., Ltd. Hyaluronic acid (HA, MW = 20000-40000 KDa, purity ≥ 99.0%) was purchased from Aladdin Chemicals Co. Ltd. Dextran (DEX, MW = 10000 Da) were purchased from Shanghai Yuanye Biotechnology Co., Ltd. Tris-base was purchased from Beijing Jintai Hongda Biotechnology Co., Ltd. Zinc nitrate hexahydrate (Zn (NO3) 2-6H2O, purity ≥ 99.0%) was purchased from Xilong Chemical Co., Ltd. Hydrochloric acid was purchased from Beijing Chemical Plant Co., Ltd. Phosphate buffer solution (PBS) was purchased from Sora Biotechnology Co., Ltd. Mouse embryonic osteoblasts (MC3T3-E1) were purchased from Shanghai Kanglang Biotechnology Co., Ltd. Staphylococcus aureus and Escherichia coli were purchased from Beina Biotechnology Co., Ltd. Anti-alkaline phosphatase (ALP), anti-osteopontin (OPN), anti-Runt-related transcription factor 2 (RUNX2), anti-osteocalcin (OCN), anti-osterix (OSX), anti-collagen type I (COL-I), anti-platelet-derived growth factor A (PDGFA) and secondary antibodies were purchased from Proteintech Biotechnology Co., Ltd.
[0037] 1.2 Methods
[0038] 1.2.1 Synthesis and characterization of nanoparticles
[0039] Taxifolin (TAX)-loaded ZIF-8 nanoparticles were synthesized using a one-pot method. Briefly, 0.36 g TAX and 0.5 g 2-methylimidazole were dissolved in 5 mL methanol solution. Then 0.1 g zinc nitrate hexahydrate was dissolved in 5 mL methanol, the two were mixed and stirred for 30 min, then centrifuged and dried to obtain TAX@ZIF-8NPs (TZ).
[0040] Take 8 mg of TAX@ZIF-8NPs and disperse them in Tris-HCl solution (10 mM, pH = 8.5), add 2 mg of dopamine hydrochloride and stir for 2 hours, then centrifuge and dry the precipitate to obtain TAX@ZIF-8@PDANPs (TZP).
[0041] The size and morphology of the nanoparticles were characterized by transmission electron microscopy (TEM, LIBRA200CS, Carl Zeiss Co, Germany). Zeta potential was measured using a Zetasizer Nano ZS90 (Malvern, UK). X-ray diffraction (XRD) analysis of the nanoparticles was performed using an X-ray diffractometer equipped with a copper sealed tube to analyze the internal crystal structure formation.
[0042] 1.2.2 Preparation and characterization of nanocomposite hydrogels
[0043] 3 g of DEX was dissolved in 100 mL of deionized water, and then 1 g of sodium periodate was added and stirred for 6 hours, and then 2 mL of ethylene glycol was added. Subsequently, it was dialyzed with deionized water for 3 days and freeze-dried to obtain ODEX.
[0044] 1g HA was dissolved in 500mL MES buffer (pH about 5.4), and then a certain amount of EDC and NHS were added to activate the carboxyl groups in HA for 4 hours. Then, 1g adipic acid dihydrazide (ADH) was added to the reaction mixture and stirred at room temperature for another 24 hours. The crude product was subjected to intensive dialysis under 0.1M NaCl and deionized water conditions. HD was obtained after freeze drying.
[0045] ODEX was dissolved in deionized water to prepare a 10% ODEX solution, and then TAX, TZ, and TZPNPs were added to the above solution and stirred. Subsequently, 3 times the amount of 5% HD aqueous solution was added to the above mixture to prepare TAX / ODEX / HD hydrogel (TG), TZ / ODEX / HD hydrogel (TZG), and TZP / ODEX / HD hydrogel (TZPG) (the TAX concentration of the three hydrogels was 250 μg / mL).
[0046] Fourier transform infrared spectroscopy (FT-IR) was used to determine the chemical composition of nanoparticles, ODEX, and HD with a scanning wave number of 400–4000 cm -1 , resolution 2cm -1 .use 1 The chemical structures of ODEX and HD were determined by HNMR. Scanning electron microscopy (SEM) images were collected at 10 kV (S4800, Hitachi, Japan).
[0047] 1.2.3 Photothermal properties of hydrogels
[0048] In order to explore the photothermal response characteristics of nanocomposite hydrogels, the present invention adopts a power density of 1.0 W / cm 2 A series of TZPG samples with different concentrations (0, 0.5, 1, 2 mg / mL) were irradiated for 10 minutes using a near-infrared laser with a wavelength of 808 nm. At the same time, a near-infrared thermal imager was used to monitor the temperature changes of each sample during irradiation in real time, and the corresponding infrared thermal imaging images were saved for analysis. To further evaluate the photostability of the TZPG group, the present invention placed the TZPG under the same parameters (1.0 W / cm 2 , 808nm) near-infrared laser on / off cycle irradiation environment, each irradiation cycle is also 10 minutes, and then it is allowed to cool naturally to room temperature. This illumination and cooling process is repeated three times. During this period, the temperature data of the sample from heating to cooling is recorded by a near-infrared thermal imager. Finally, according to the provided formula (1, 2), the acquired data is calculated to obtain the photothermal conversion efficiency (η) of TZPG.
[0049]
[0050] Where I is the power density of the laser (1W / cm 2 ), A 808 is the absorbance at 808 nm (0.443), Q diss is the heat gained by the quartz cell under irradiation (21.3 mW), ΔT max is the temperature change, ΔT max =T max -T surr =30.4℃; T max is the maximum temperature under irradiation, T surr is the ambient temperature;
[0051] To obtain hS, the following formula is used:
[0052] hS=∑ i m i C p,i tlnθ (2)
[0053] Where, m is the mass of the hydrogel (1 g), C p is the specific heat capacity of the measured material (4.2 Jg -1 ℃ -1 ); T is the time of heating and cooling before and after irradiation, ts is the slope of the linear regression equation of -lnθ and T; i is the number of sampling times;
[0054] 1.2.4 Drug Release
[0055] In order to explore the in vitro drug release characteristics of the hydrogel, the present invention first accurately added 1 mL of the nanocomposite hydrogel into 5 mL of PBS solution with a pH value of 7.4. It was placed in a constant temperature shaker, and a portion of the liquid was taken at preset time intervals, and the release process of TAX was quantitatively monitored using UV-VIS spectroscopy. The cumulative release percentage of TAX was further calculated to quantitatively evaluate the drug release efficiency of the hydrogel. The specific calculation formula is as follows:
[0056]
[0057] Among them, V d is the replacement volume of PBS (5 mL), V is the volume of the release solution PBS (5 mL), C i is the concentration of TAX in the release solution during the i-th sample exchange (μg / mL), m s is the mass of TAX in the drug delivery material for release (μg), and n is the number of replacements of PBS.
[0058] 1.2.5 Degradation and swelling properties
[0059] The in vitro swelling and degradation performance of nanocomposite hydrogels were tested using the gravimetric method. Simply put, a certain amount of hydrogel sample was weighed and completely immersed in PBS buffer solution. The hydrogel was then taken out and weighed at a specific time point. The swelling and degradation were evaluated by calculating the mass ratio of the hydrogel before and after.
[0060] 1.2.6 Mechanical properties of hydrogels
[0061] 1.2.6.1 Rheological tests
[0062] The storage modulus (G') and loss modulus (G") of the hydrogel samples were measured using an Anton Paar instrument (Physica MCR301, Germany) to obtain the rheological properties of the samples. When the strain was 1%, the angular frequency functions of G' and G" were measured at 25 °C and a sweep frequency of 1 to 100 rad / s. In addition, the angular frequency functions of G' and G" were measured at a strain of 1% and a sweep frequency of 1 to 100 rad / s. -1 A shear rate scan with a frequency of 10.0 rad / s was measured in the range to characterize the shear thinning behavior of the hydrogel.
[0063] 1.2.6.2 Adhesion test
[0064] The present invention uses a universal testing machine to investigate the bonding strength of the hydrogel at room temperature. The pigskin is cut into rectangles of 1 cm × 1 cm. The hydrogel is then placed between two pieces of fresh pigskin. The covering speed is 10 mm / min.-1 The pigskin covering the overlapping parts was completely separated according to the operation steps, and the maximum bonding strength was measured.
[0065] 1.2.7 Invitroactivity studies
[0066] 2.2.7.1 Antibacterial activity
[0067] In order to test the in vitro antibacterial efficiency of each group of hydrogels against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), Staphylococcus aureus and E. coli were placed in autoclaved LB liquid culture medium and cultured overnight at 37°C in a shaking incubator. TG (200 mg), TZG (200 mg), and TZPG (200 mg) hydrogels were mixed with diluted bacterial suspensions (S. aureus and E. coli, 800 μL, 1×10 7 CFU / mL) were added to a 24-well plate (the wells without samples were used as the control group), and after irradiating the TZPG group with NIR for 10 minutes, they were placed in a 37°C incubator for 2 hours. The bacterial suspension (30 μL) of each group was evenly spread on the surface of the corresponding LB solid culture medium plate, and photographed and counted after a period of incubation.
[0068] 1.2.7.2 Antioxidant activity
[0069] In order to study the antioxidant activity of the hydrogel, the present invention detected the scavenging ability of ABTS free radicals by adding the hydrogel extract to 3 mL of ABTS working solution. The culture was carried out in the dark. The ABTS solution without adding the hydrogel extract and the control were used as controls. The absorbance of the solution was measured at a wavelength of 734 nm.
[0070] The scavenging ability of DPPH free radicals was also tested. The hydrogel extract was added to 3 mL of DPPH ethanol solution (0.1 mM) and cultured in a dark environment. The DPPH solution without the addition of hydrogel extract was used as the control group. The absorbance of the solution was measured at a wavelength of 517 nm.
[0071] 1.2.7.3 Hemolysis test
[0072] In order to evaluate the compatibility of hydrogel with blood, the hydrogel was added to whole blood and incubated at 37°C for 60 minutes, and then the absorbance was measured at a wavelength of 545 nm. The negative and positive controls were composed of PBS and TritonX-100, respectively, and the hemolysis rate was calculated as follows:
[0073]
[0074] Among them, OD s is the absorbance of the test sample, OD n and OD p Represent the absorbance of negative control and positive control, respectively.
[0075] 1.2.7.4 Cell culture and proliferation assay
[0076] Mouse embryonic osteoblasts (MC3T3-E1) were cultured in α-MEM medium containing 10% fetal bovine serum and 1% penicillin-streptomycin, and the incubator was set at 37°C and 5% CO2. The cells were divided into 4 groups after 4 different treatments, including untreated group (Control) and TG, TZG, and TZPG+NIR. To evaluate the cell viability and biocompatibility of the hydrogel, the colorimetric 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium bromide (MTT) method was used for determination after 1, 3, and 5 days of corresponding treatment.
[0077] 1.2.7.5 Osteogenic differentiation of MC3T3 cells
[0078] MC3T3-E1 cells were cultured in osteogenic medium containing 10% FBS, 0.1 μM dexamethasone, 10 mM β-glycerophosphate and 50 μg / mL ascorbic acid. After the cells were fixed, each group was treated differently and then stained with Alizarin Red (ARS) on day 21.
[0079] 1.2.8 In vivo experiments
[0080] 1.2.8.1 Animal culture
[0081] Special feed and sterile water were used during animal feeding, and sufficient supply was ensured; animal bedding was changed every 2-3 days; the animal room was disinfected and cleaned once a week; all experiments were conducted after the animals entered the feeding environment and adapted for 1 week. A total of 40 SD female rats (about 200-250g) were selected for the experiment, and the rats were randomly divided into four groups: blank (no treatment was done on the defect), TG, TZG, and TZPG+NIR. Before surgery, 10% chloral hydrate was injected intraperitoneally for anesthesia. After sufficient anesthesia, the skin of the rat's brain was cut open with a scalpel to expose the skull, and a 5mm steel circular trephine was used to form two equal-sized circular bone defects symmetrically on the left and right sides of the skull. The hydrogels prepared in each group before surgery were implanted into the corresponding defect sites, and the incisions were sutured layer by layer after implantation. Within 3 days after surgery, the rats were given intramuscular injections of penicillin every day to prevent postoperative infection. Then near-infrared light (808nm, 1W / cm 2 ) The surgical defect area was irradiated for 10 minutes every 7 days, and an infrared thermal camera was used to monitor and record temperature changes in real time.
[0082] 1.2.8.2 Micro-CT analysis
[0083] In order to analyze the formation of new bone at the defect site after 8 weeks, the present invention performed Micro-CT analysis on rat skull samples. At 8 weeks after surgery, the rats were killed to collect the rat skull samples, which were fixed with 4% paraformaldehyde and then scanned and analyzed using a micro-computed tomography scanner Micro-CT.
[0084] 1.2.8.3 Histopathological staining
[0085] In order to observe the promoting effect of each group of hydrogel on bone regeneration, the present invention performs Hematoxylin-eosin and Masson's trichrome staining. The skull tissue is fixed with 4% paraformaldehyde, dehydrated, and then transferred to a xylene solution for immersion until the tissue is transparent. After paraffin embedding, the sections are processed and stained, and finally an optical microscope is used to observe the pathological changes of the skull tissue.
[0086] 1.2.8.4 Immunofluorescence staining
[0087] To further evaluate the effects of each group of hydrogels on new bone formation, the present invention used immunohistochemistry to detect skull samples. First, the paraffin sections of skull tissue were dewaxed and then subjected to antigen repair. The first antibody was applied after blocking the nonspecific binding sites, and then the second antibody was applied. The sections were observed and photographed, and the positive staining areas were quantitatively analyzed.
[0088] 1.2.8.5 Westernbolt analysis Westernbolt analysis
[0089] The total protein of the skull sample was lysed and the protein was extracted from it. Antibodies against osteogenic factors Alkaline Phosphatase (ALP), Runt-related transcription factor 2 (RUNX2), Osterix (OSX), Osteocalcin (OCN), Collagen Type I (COL-I) and Platelet Derived Growth Factor Alpha (PDGFA) were incubated with PVDF membrane at 4°C for 12 hours, and then the PVDF membrane was incubated with secondary antibodies for 1 hour. Finally, the protein bands on the membrane were visualized using an enhanced chemiluminescence kit, and the signals were detected using a Western blot detection system.
[0090] 1.2.8.6 Statistical analysis
[0091] To ensure the reliability of the experimental results, each experiment was repeated at least three times, and the experimental results were finally presented in the form of mean and standard deviation (SD). In addition, the present invention first performed a normal distribution test on the collected data, and then used a one-way analysis of variance (ANOVA) method and subsequent multiple comparison tests to strictly determine the significant differences between the groups of data. If p<0.05, the difference was considered significant. (*p<0.05, **p<0.01 or ***p<0.001).
[0092] 2. Results
[0093] 2.1 Synthesis and characterization of nanoparticles
[0094] TEM was used to characterize the morphology of ZIF-8, TZ and TZP. Figure 1As shown in A, ZIF-8 has a cubic geometry, uniform particle size and exists in a single dispersed state. From the TEM of TZ, it can be seen that TAX encapsulated in ZIF-8 has a unique rhombic dodecahedron structure of ZIF-8. Compared with TZ, the particle size of TZP is larger, and the edges of the rhombic dodecahedron structure of TZP are blurred, with a gray translucent shell layer and an increased thickness, indicating that DA successfully forms a PDA coating on the surface of TZ through oxidative self-polymerization. The present invention uses XRD to conduct an in-depth study on the crystal structure information of four materials: ZIF-8, TZ, TZP, and TAX ( Figure 1 B). The results show that the XRD spectrum of ZIF-8 nanocrystals is consistent with the theoretical simulation spectrum. In addition, the study found that the in-situ loading of TAX in ZIF-8 does not significantly affect its crystal structure, and its characteristic peaks have been retained in the XRD patterns of TZ and TZP composites, so it can be determined that the preparation of TZP composites is successful. Zeta potential is used to characterize the surface charge of nanoparticles and obtain information about their stability and surface interactions with other molecules. PDA converts the TZ particles from positive to negative after coating. The coating is a polymer containing a large amount of phenolic hydroxyl groups, and the deprotonation of phenolic groups makes the PDA molecules negatively charged. When the synthesized nanoparticles have a relatively large positive or negative ζ value (>±30mV), the particle solution stability is better because the surface charge of the particles is strong enough to overcome the van der Waals force and is conducive to dispersion in the solution. PDA coating can not only improve the dispersibility of TZ particles and realize the surface functionalization of TZ particles, but also slowly control the release of the loaded drug (TAX), providing a new idea for drug-loaded bone tissue engineering.
[0095] 2.2 Preparation and characterization of nanocomposite hydrogels
[0096] The infrared spectra of ZIF-8, TAX, TZ and TZP are shown in Figure 2 A. For ZIF-8 nanoparticles, 1145 cm -1 and 994cm -1 The peak at 3550cm corresponds to the bending vibration of the imidazole ring, which is its characteristic absorption peak. In addition, by comparing the infrared spectrum of ZIF-8 nanoparticles, the characteristic peak of ZIF-8 also exists in TZ. In the infrared spectrum of TZP nanoparticles, at 3550cm -1 The peak at 1660 cm-1 is enhanced and broadened, which is due to the OH stretching vibration of PDA. -1The corresponding part is the stretching vibration of the carbonyl C=O in the PDA functional group. The above results show that PDA was successfully attached to the surface of ZIF-8 nanoparticles, and TAX-loaded ZIF-8@PDA core-shell particles were successfully prepared. During bone regeneration, the soft and moist surface of the hydrogel can greatly reduce the adverse effects of the material on surrounding tissues, and it is easy to administer drugs to achieve continuous local drug release. The present invention uses HA and DEX as the matrix and particles to prepare porous hydrogels. Figure 2 In B, ODEX can be observed at 1732 cm -1 The new characteristic peak at is the stretching vibration peak of the aldehyde group (C=O). Compared with the FT-IR spectrum of DEX, it is found that there is no such peak, indicating that some of the hydroxyl groups in the DEX structure have been oxidized to aldehyde groups. Figure 2 It is clearly seen in C that a new characteristic peak appears near δ = 9-10 ppm, which corresponds to the hydrogen peak of -CHO. This indicates that dextran has generated an aldehyde group, that is, dextran has been successfully oxidized by sodium periodate. Figure 2 In D), compared with the spectra of HA and ADH, the spectrum of HA-ADH contains not only the specific absorption peak of the hydrazide bond NH of ADH at 3316 cm -1 The HA polysaccharide alcohol hydroxyl -OH angle vibration absorption peak 1037cm -l , and a new absorption peak appeared at 1636 cm -1 This characteristic peak is related to the angle vibration of -NH2, which confirms the successful grafting of ADH and HA. 1 In the HNMR spectrum, HA-ADH showed a new peak corresponding to the proton of ADH ( Figure 2 E) FT-IR and 1 The results of HNMR spectra showed that dextran and hyaluronic acid were successfully modified. Then ODEX and HD aqueous solutions were mixed to prepare hydrogels, and effective aldehyde hydrazine covalent cross-linking reactions promoted the formation of hydrogels. As a tissue engineering scaffold, the hydrogel should be porous because an interconnected porous network is conducive to the entry of oxygen and nutrients and the discharge of metabolites. Scanning electron microscopy ( Figure 2 F) It can be seen that each group of hydrogels is loose and porous. This loose and porous internal morphology is conducive to the transport of internally loaded drug molecules, thereby effectively promoting bone repair.
[0097] 2.3 Physicochemical characterization and mechanical properties of nanocomposite hydrogels (drug release, degradation, swelling, rheology, adhesion)
[0098] As a suitable and potential drug delivery carrier, hydrogel can gradually release TAX into body fluids through degradation rather than diffusion, which can better achieve effective drug release. However, due to the low bioavailability of TAX, it cannot be completely absorbed by the body. Therefore, the present invention adopts nanoformulation technology to improve its low bioavailability. Figure 3 As shown in A and B, the TG group will release suddenly in the early stage and then reach equilibrium. The drug loading (DLC) of TZ is 25%. Compared with the TG group, the TZG group and the TZPG+NIR group better maintained the long-term release behavior and could release for up to 30 days. Biodegradable biomaterials play an increasingly important role in the treatment of bone defects. This material can provide a bridge for new bone tissue in the gap and a platform for drugs to act. The platform will eventually degrade and absorb in the body and become replaced by new bone tissue. At the same time, there was no significant difference in the swelling rate of each group ( Figure 3 C), which showed that all groups had good swelling properties, were able to absorb tissue exudates, and fully fill the defect. The adhesion strength of the hydrogel was tested by the pig skin tissue lap shear test ( Figure 3 D), the results showed that each group of hydrogels had good adhesion ability. However, compared with the TZG group, the adhesion ability of the TG group was enhanced, which may be due to the formation of more hydrogen bonds between the abundant phenolic hydroxyl groups on the TAX surface and the amine and thiol groups on the tissue surface. The adhesion of TZPG is the strongest among the three groups of hydrogels, which is considered to be the result of the synergistic effect of PDA and the hydrogel substrate, giving it excellent adhesion. When the angular frequency increased from 0.1rad / s to 100.00rad / s, the G' values of the three groups of hydrogels were all greater than G", indicating that each group of hydrogels has always maintained a gel state ( Figure 3 E). At the same time, under the condition of 1% stress, the G' and G" of each group of hydrogels basically changed little with the increase of time ( Figure 3 F), this result shows that each group of hydrogels has good mechanical strength, flexibility and stability. In summary, TZPG is a bioadhesive biomaterial that promotes bioadhesion between bone implants and hosts, accelerates the osteogenesis process, and is a promising bone implant.
[0099] 2.4 Photothermal properties of nanocomposite hydrogels
[0100] In the process of tissue regeneration, an ambient temperature of 40-45°C can produce a "spa effect", thereby effectively increasing the speed of nutrient delivery in blood vessels. Therefore, the present invention tests the photothermal effect of hydrogels with different TZPNPs concentrations under the same near-infrared irradiation power. It can be seen that ( Figure 4AE), the final temperature of the hydrogel with different ion concentrations is proportional to the time, and the temperature can be controlled by adjusting the particle concentration. At 10 minutes, the temperature of the 1mg / mT ZPG group can rise to 45.1°C, while in the blank hydrogel (BG) group, the temperature of the hydrogel increased by 2.8°C. After stopping the irradiation, the TZPG group showed a gradual cooling characteristic, indicating that the hydrogel has a certain heat storage capacity. The present invention further evaluated the photothermal stability of this composite hydrogel. In three irradiation cycles with almost the same temperature distribution, the TZPG group showed a higher photothermal response stability ( Figure 4 E), indicating that TZPG can be repeatedly irradiated and has long-term photothermal conversion function. By calculation, the photothermal conversion efficiency (η) of TZPG is 51.79%. TZPG with high photothermal conversion efficiency converts light energy into thermal energy and promotes bone regeneration at low power. The above results verify that TZPG has good photothermal activity and lay the foundation for its application in comprehensive photothermal therapy.
[0101] 2.5 In vitro activity of nanocomposite hydrogels (antibacterial and antioxidant)
[0102] In addition to having excellent osteoinductive properties, ideal bone repair materials should also have excellent antibacterial ability. The aromatic ring of PDA plays an antibacterial role, but the main antibacterial activity of PDA comes from photothermal therapy (PTT), which converts light energy into thermal effects through photothermal materials, damaging cell membranes or denaturing proteins, and subsequently causing bacterial death. However, pure PDA coatings have limitations in antibacterial ability and cannot achieve efficient and stable antibacterial effects. Therefore, it is often necessary to compound with antibacterial substances. In addition, previous studies have pointed out that a single antibacterial method is not efficient, and the high temperature required for a single antibacterial strategy may also cause damage to surrounding healthy tissues. Therefore, the present invention chooses to coat PDA on TAX@ZIF-8. TAX itself has excellent antibacterial properties, and the antibacterial ability of ZIF-8 has also been confirmed. Zn in ZIF-8 2+ The antibacterial mechanism of chloramphenicol is to disrupt the homeostasis in bacteria, enhance the permeability of protons to bacterial membranes, and thus inhibit bacterial glycolysis and polysaccharide synthesis. Figure 5As shown in B, compared with the control group, the inhibition rates of TG, TZG, and TZTG+NIR against Escherichia coli were 76.25±0.58%, 88.89±1.16%, and 96.93±0.36%, respectively. The inhibition rates of each group against Staphylococcus aureus were 69.83±1.88%, 89.43±1.33%, and 99.63±0.13%. The results showed that the TZTG+NIR group had the most significant antibacterial effect, whether it was Gram-negative or Gram-positive bacteria. During bone healing, in addition to having efficient antibacterial properties, it is also necessary for bone implants to be able to scavenge excessive reactive oxygen free radicals. Excessive reactive oxygen in the process of bone regeneration will have a negative impact on it and may inhibit the differentiation process of osteoblasts. The antioxidant activity of the hydrogel was evaluated by the scavenging rate of DPPH and ABTS free radicals. Figure 5 As shown in C, the scavenging effect on ABTS free radicals, IC values of TG, TZG and TZTG+NIR 50 The values were 5.15±0.07ug / mL, 4.91±0.02ug / mL and 6.36±0.15ug / mL, respectively. 50 The lower the value, the stronger the antioxidant activity, thus showing the significant efficacy of each group of hydrogels in scavenging ABTS free radicals. DPPH is usually evaluated by accepting hydrogen or electrons. Figure 5 As shown in D, TZTG+NIR showed stronger DPPH free radical scavenging activity, IC 50 The value was 13.66±0.12μg / Ml; while the IC 50 The values were 25.21±2.44μg / mL and 33.71±0.25μg / mL, respectively. The results showed that TZTG+NIR exhibited good antioxidant properties, and its ability to neutralize DPPH free radicals was significantly better than that of TG and TZG, suggesting that the nanohydrogel formulation has potential in enhancing antioxidant defense. This positive effect on free radical neutralization may be beneficial for improving the ability to occur oxidative stress during bone regeneration.
[0103] 2.6 Biocompatibility and in vitro osteogenic differentiation of nanocomposite hydrogels
[0104] In order to evaluate the biocompatibility of each group of hydrogels, this experiment conducted tests on their hemolysis and cytotoxicity. If the blood compatibility of the material injected into the body is poor, it may cause a hemolytic reaction, thus endangering life safety. The hemolysis test is an important indicator for evaluating its blood toxicity. Therefore, hemolysis testing must be performed when developing new biomaterials. Figure 6As shown in A. For all the hydrogels tested in this study, the percentage of hemolyzed red blood cells was less than 5%. Biomaterials with a hemolysis rate of less than 5% meet international standards and can be used as blood contact materials. Therefore, the results of this experiment show that each group of hydrogels has good blood compatibility. The MTT method was used to determine the proliferation effect of each group of hydrogels on MC3T3-E1. Figure 6 As can be seen from B, on days 1, 3, and 5, the TG, TZG, and TZPG+NIR groups all promoted cell proliferation and growth, and the proliferation rate of the TZPG+NIR group was faster, thereby promoting bone tissue formation.
[0105] Osteoblasts are the key to matrix deposition and mineralization. Matrix mineralization, as the final step of osteoblast differentiation, is a key indicator for evaluating the effectiveness of osteoblast differentiation. Alizarin red staining can be used to measure its mineralization ability. According to the experimental results ( Figure 6 C) showed that the TZPG+NIR group had significantly enhanced the mineralization potential of osteoblasts and formed more calcium nodules than the control group.
[0106] 2.7 Osteogenesis of nanocomposite hydrogels in vivo
[0107] According to the in vitro experimental results, the hydrogel was implanted into the critical bone defect of rat skull ( Figure 7 A). Apply near-infrared irradiation to the defect every seven days for 8 weeks after surgery ( Figure 7 B), to study its in vivo osteogenic potential. Each group of experimental rats was killed 8 weeks after surgery, and then their skull samples were collected. Micro-CT scanning, H&E and Masson staining and immunohistochemical analysis were performed on the bone defect area. Micro-CT technology has its unique advantages in evaluating trabecular bone, cortical bone, etc., and is currently considered to be the "gold standard" for bone microstructure and morphology. Inspired by the results of in vitro experiments, the present invention further studied the repair effect of this material on a severe bone defect model in rats. In the CT scan images, no residue of the material was observed, proving that the material has good biodegradability and will not affect new bone formation. Compared with the control group, the new bone tissue in the TG, TZG and TZPG+NIR groups all increased to varying degrees, among which the bone tissue in the TZPG+NIR group was the most generated and had the highest density. Bone density cannot fully reflect changes in bone strength, and trabecular microstructure is the most important factor affecting bone strength and its function. Therefore, this study quantitatively analyzed the microstructure of the skull and analyzed the changes in bone volume fraction (BV / TV), trabecular number (Tb.N), trabecular thickness (Tb.Th), and trabecular spacing (Tb.Sp). Figure 7DG). The number and thickness of trabeculae in the TG, TZG and TZPG+NIR groups increased to varying degrees compared with the control group. Unlike the increase in Tb.N and Tb.Th, the trabecular spacing in the three groups decreased compared with the control group, with Tb.Sp being 3.74±0.29mm, 2.24±0.33mm, and 0.47±0.003mm, respectively. At the same time, the BV / TV of the defects in the three groups reached 16.20±3.26%, 26.62±1.04%, and 67.12±8.43%, respectively. In summary, compared with the control group, the TG, TZG and TZPG+NIR groups all showed increased new bone formation, increased number of trabeculae, thicker trabeculae, and reduced trabecular spacing. It is worth noting that the TZPG+NIR combination showed an extremely excellent osteogenesis effect in the above results, which means that the composite hydrogel can achieve a therapeutic effect after light exposure and can effectively promote bone regeneration in the rat bone defect model while minimizing the damage to healthy tissues caused by excessive heat production.
[0108] 2.8.1 Histological and immunohistochemical analysis
[0109] Histological sections are also used to evaluate the quality of bone tissue filling the defect site and to show bone morphology and microstructure. As shown in the cross section of the decalcified skull ( Figure 8 A), compared with the control group where fibrous connective tissue (FT) occupied most of the defect site, the proportion of new bone tissue (NB) in the TG, TZG and TZTG+NIR groups was larger, and the regenerated bone in the TZTG+NIR group was more mature. This is consistent with the results of CT analysis, showing a therapeutic effect in promoting bone regeneration. No obvious substances were found, indicating that the material had been completely degraded. And the TG, TZG and TZTG+NIR groups all showed good biocompatibility, and no obvious inflammatory cells were found in the peripheral bone tissue.
[0110] The activity of alkaline phosphatase (ALP) is recognized as one of the important means to evaluate the activity of osteoblasts. As a marker of osteoblast characteristics and a typical product of the differentiation process, its importance is self-evident. Osteopontin (OPN) is one of the non-collagen proteins that constitute the bone matrix. It is abundant in osteoblasts and osteoclasts and has a significant effect on promoting the maturation of osteoclasts and their absorption function. It is worth noting that type I collagen (COL-I), as a key extracellular matrix component, is directly related to the quality and mechanical strength of bone tissue. In addition, Runt-related transcription factor 2 (RUNX2) plays a core regulatory role and is essential for regulating the gene expression of osteoblast-specific matrix proteins including ALP, COL-I, OPN, etc., thereby ensuring the smooth progress of the bone mineralization process. Eight weeks after surgery, compared with the control group, the expression of ALP in the skull of rats in the TZTG+NIR group was significantly increased ( Figure 8B, C), indicating that osteoblast differentiation ability is strong; the expression of RUNX2 is significantly increased ( Figure 8 B, D), indicating that the ability to promote mineralization of bone tissue nodules is significant. The OPN positive expression area increased significantly ( Figure 8 B, E), indicating that there are more positively stained osteocytes in the new bone tissue, indicating a higher osteogenic activity. The COL-I positive staining areas in the TG, TZG and TZTG+NIR groups were significantly more than those in the control group ( Figure 8 B, F), indicating excellent bone quality. In summary, we believe that this new smart hydrogel can effectively promote the ingrowth of bone tissue in three-dimensional space, as well as continuously release TAX during bone regeneration, accelerating the formation of new bone.
[0111] 2.8.2 Western blot analysis
[0112] ALP plays a key role in the early differentiation of osteoblasts. Osteocalcin (OCN) is a marker substance that appears in the late stage of osteoblast differentiation and can bind to Ca 2+ Combined with, it participates in regulating calcium ion balance and bone mineralization. Osterix (OSX), as an osteoblast-specific transcription factor, is an indispensable factor to ensure normal bone development. At the same time, the two major transcription factors, RUNX2 and OSX, jointly take on the important task of driving cells to differentiate into the osteoblast lineage. Among them, during early bone formation, the activity of RUNX2 is particularly critical for osteoblast differentiation. Type I collagen (COL-I), as the main component of the extracellular matrix, not only promotes the adhesion of osteoblasts, but also actively mediates their differentiation process. In addition, platelet-derived growth factor (PDGFA) plays an important role in the fracture healing mechanism, and its expression at the site of injury can accelerate the repair process. PDGFA effectively promotes the regeneration and healing of bone tissue by attracting and stimulating the proliferation of osteoblast progenitor cells. Compared with the control group, the expression levels of osteogenic-related proteins ALP, RUNX2, OSX, OCN, COL-I, and PDGFA in the TG, TZG, and TZTG+NIR groups increased to varying degrees, among which the increase in the TZTG+NIR group was the most significant ( Fig. 9 AG). This indicates that the synergistic treatment of TZTG and near-infrared light can not only promote osteoblast proliferation and differentiation, but also participate in regulating Ca 2+ homeostatic environment, and accelerate wound healing and bone tissue regeneration.
[0113] The present invention successfully prepared a photoresponsive bone-targeted intelligent nano-delivery system (TZPG), which loaded PDA on the surface of nanoparticles to form a coating, and presented it to the bone defect site through an implant (hydrogel), exerting its functions of long-term drug release, staged photothermal antibacterial and biomineralization to promote bone healing. It not only has a high photothermal conversion efficiency (η=51.79%), but also can release drugs for more than 30 days, and has good biocompatibility, biodegradability and bioadhesion. At the same time, under 808nm laser irradiation, the TZPG scaffold can not only maintain good photothermal induced antibacterial ability, but also significantly promote the proliferation and osteogenic differentiation of MC3T3-E1 cells.
[0114] The above description is a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A hydrogel with good bioadhesion, characterized in that: The hydrogel is prepared into a loose and porous hydrogel by reacting oxidized dextran with hyaluronic acid modified with adipic acid dihydrazide through a Schiff base reaction, and TAX@ZIF-8@PDA is loaded in the hydrogel. The preparation method of the TAX@ZIF-8@PDA is as follows: firstly encapsulating TAX in ZIF-8 nanoparticles to obtain TAX@ZIF-8 nanoparticles; then wrapping PDA on the surface of the TAX@ZIF-8 nanoparticles; wherein TAX is dihydroquercetin, ZIF-8 is a zinc-based zeolite imidazole skeleton, and PDA is polydopamine.
2. A method for preparing a hydrogel with good bioadhesion, characterized in that: The method comprises the following steps: Step 1. First, TAX is encapsulated in ZIF-8 nanoparticles to obtain TAX@ZIF-8 nanoparticles; then, PDA is coated on the surface of TAX@ZIF-8 nanoparticles to obtain TAX@ZIF-8@PDA; Step 2. Using oxidized dextran aqueous solution and adipic acid dihydrazide-modified hyaluronic acid aqueous solution as the matrix, TAX@ZIF-8@PDA was added to 10% oxidized dextran aqueous solution, followed by adding 3 times the amount of 5% adipic acid dihydrazide-modified hyaluronic acid aqueous solution to prepare a hydrogel with good bioadhesion.
3. The method for preparing a hydrogel with good bioadhesion according to claim 2, characterized in that: In step 1, TAX@ZIF-8 nanoparticles were prepared by dissolving 0.36 g of TAX and 0.5 g of 2-methylimidazole in 5 mL of methanol solution; Then, 0.1 g of zinc nitrate hexahydrate was dissolved in 5 mL of methanol, and the two were mixed and stirred for 30 min, followed by centrifugation and drying of the precipitate to obtain TAX@ZIF-8NPs. The preparation method of TAX@ZIF-8@PDA is as follows: 8 mg of TAX@ZIF-8NPs are dispersed in a Tris-HCl solution, 2 mg of dopamine hydrochloride is added, stirred for 2 h, centrifuged, and the precipitate is dried to obtain TAX@ZIF-8@PDA NPs.
4. The method for preparing a hydrogel with good bioadhesion according to claim 2, characterized in that: In step 2, the preparation method of hyaluronic acid modified with adipic acid dihydrazide is as follows: 1 g of HA is dissolved in 500 mL of MES buffer, and then EDC and NHS are added to activate the carboxyl groups in HA for 4 hours; then, 1 g of adipic acid dihydrazide is added to the reaction mixture, and stirred at room temperature for another 24 hours; the crude product is subjected to enhanced dialysis under 0.1 M NaCl and deionized water conditions, and freeze-dried to obtain HD, i.e., HA modified with adipic acid dihydrazide.
5. The method for preparing a hydrogel with good bioadhesion according to claim 2, characterized in that: The TAX concentration in the hydrogel with good bioadhesion is 250 μg / mL.
6. Use of the hydrogel with good bioadhesion according to claim 1 in preparing a biological scaffold for promoting bone repair.
7. Use of the hydrogel with good bioadhesion as claimed in claim 1 in the preparation of photothermal conversion materials.
Citation Information
Cited By
Organic framework microgel for relieving osteoarthritis and application thereof
CN121489859A